Numerical Ranges of Normal Weighted Composition Operators on the Fock Space of CN. (3rd September 2018) - Lang, Lili; Zhao, Liankuo
Abstract : Numerical ranges of normal weighted composition operators on the Fock space ofC N are completely characterized. The main result shows that numerical ranges of such operators are closely related to their composition symbols.